Clinical Profiles and Types of Senile Cataract Patients: Experience of 30 Cases in Bangladesh - Sultana, Shamima; Sharif, AQM Omar; Choudhury, Inamur Rahman; Haque, MM Ehsanul; Begum, Wahida (Journal of Current and Advance Medical Research, 2019)
Background: Senile cataract can be expressed with different clinical presentation. Objective: The purpose of the present study was to find out the clinical profiles of senile cataract patients. Methodology: This cross-sectional study was conducted at National Institute of Ophthalmology, Dhaka, Bangladesh from January 1999 to December 2000 for a period of two (02) years. Patients with senile cataract were selected for study. The details clinical profiles of the study population were recorded like types, grades of cataract and visual acuity. Data were collected on pre-designed data collection sheet, compiled and appropriate statistical analysis was done using computer based software. Result: A total number of 60 eyes of cataract patients were recruited for this study. The mean age with the standard deviation was 58.8±6.055 years. Majority of the patients were suffering from total cataract that is nuclear plus cortical plus posterior subcapsular variety which was 31(51.7%) eyes of cataract patients. Majority of the patients were grade III (amber) type of nuclear sclerosis which was 26(43.3%) eyes of cataract patients. Most of the patients were presented with PL which was 32(53.3%) eyes of cataract patients. Conclusion: In conclusion majority of the patients are suffering from total cataract with grade III (amber) type of nuclear sclerosis. Journal of Current and Advance Medical Research 2019;6(1):38-41